STRUCTURE AND INDIVIDUAL ANATOMICAL VARIABILITY OF THE LOBULE IX OF THE HUMAN CEREBELLAR HEMISPHERES - Maryenko, N.I.; Stepanenko, O.Yu. (World of Medicine and Biology, 2016)
The structure of the lobule IX of cerebellar hemispheres (cerebellar tonsils) was investigated. Research was conducted on 100 cerebellums of people of both sexes. Parasagittal sections of cerebellar hemispheres were investigated.The shape and structure of the particles depends on the width of the cerebellum and may differ in parasaggital sections depending on angle of the section plane. It was established that dichotomously branched white matter is the basis of the structure of the lobule, which may include from 4 to 9 main branches. Most often occurs between 5 and 7 branches of white matter. Medio-lateral size of lobules was investigated, most of the cerebellar tonsils do not reach the parasaggital section located at a distance of 15 mm from the median plane. Described variants of the shape of the cerebellar lobules can be used as criteria standards of modern diagnostic imaging techniques for the diagnosis of various diseases of the CNS.